Faktor Kognitif dan Non-kognitif pada Kemampuan Penalaran Matematis Siswa di Sekolah Dasar: Systematic Literature Review (SLR) - Faizzah, Atika Rahma; Surya, Anesa (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Mathematical reasoning skills are important for students because they play a role in helping them solve problems and think logically. The purpose of this study is to systematically review the literature on the importance of mathematical reasoning skills in elementary schools. This study, using the Systematic Literature Review (SLR) method, analyzes articles published between 2023 and 2024 from the Google Scholar database. The findings show that students’ mathematical reasoning skills are influenced not only by cognitive factors but are also closely related to non-cognitive aspects such as students’ attitudes toward mathematics (mathematical disposition), self-efficacy, and learning discipline. Therefore, it is important for teachers to apply student-centered learning approaches that go beyond verbal instruction and provide opportunities for idea exploration, collaborative problem-solving, and reflection on students' thinking processes.Kemampuan penalaran matematis penting untuk dimiliki oleh siswa karena berperan dalam membantu menyelesaikan masalah dan berpikir logis. Tujuan dari penelitian ini adalah untuk mengkaji literatur secara sistematis mengenai pentingnya kemampuan penalaran matematika di sekolah dasar. Penelitian dengan metode Systematic Literature Review (SLR) ini menganalisis artikel-artikel yang diterbitkan pada tahun 2023-2024 menggunakan database Google Scholar. Hasil pada penelitian menunjukkan bahwa kemampuan penalaran matematis siswa tidak hanya dipengaruhi oleh faktor kognitif saja, tetapi juga berkaitan erat dengan aspek non-kognitif seperti sikap siswa terhadap matematika (disposisi matematis), efikasi diri, serta kedisiplinan dalam belajar. Dengan demikian, penting untuk guru menerapkan pendekatan pembelajaran yang berpusat pada siswa, yang tidak hanya menyampaikan materi secara verbal, tetapi juga memberi ruang untuk eksplorasi ide, pemecahan masalah secara kolaboratif, serta refleksi terhadap proses berpikir yang dilakukan siswa.